2019
DOI: 10.1038/s42003-019-0636-7
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod controls vegetation phenology across Africa

Abstract: Vegetation phenology is driven by environmental factors such as photoperiod, precipitation, temperature, insolation, and nutrient availability. However, across Africa, there’s ambiguity about these drivers, which can lead to uncertainty in the predictions of global warming impacts on terrestrial ecosystems and their representation in dynamic vegetation models. Using satellite data, we undertook a systematic analysis of the relationship between phenological parameters and these drivers. The analysis across diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 63 publications
0
37
1
1
Order By: Relevance
“…Finally, our results seem to contrast earlier research which has shown that phenology of cropland and grassland in sub-Saharan Africa is mainly driven by photoperiodicity, while in our model a longer rainy season will cause a longer growing season (Adole et al, 2019). Photoperiodicity is only implemented for crop PFTs in LPJ-GUESS, while for the natural vegetation PFTs that were used in this study, simulated phenology is driven by water availability and therefore follows the rainy season.…”
Section: Response Of Woody Versus Herbaceous Covercontrasting
confidence: 91%
“…Finally, our results seem to contrast earlier research which has shown that phenology of cropland and grassland in sub-Saharan Africa is mainly driven by photoperiodicity, while in our model a longer rainy season will cause a longer growing season (Adole et al, 2019). Photoperiodicity is only implemented for crop PFTs in LPJ-GUESS, while for the natural vegetation PFTs that were used in this study, simulated phenology is driven by water availability and therefore follows the rainy season.…”
Section: Response Of Woody Versus Herbaceous Covercontrasting
confidence: 91%
“…Knowledge of what controls the present-day seasonality of basin evaporation would provide a point of reference with which to compare climate and ecosystem models. This evaluation would determine whether these models produce the correct seasonality of evaporation for the right reasons (Maeda et al 2017;Adole et al 2019). Additionally, without a robust understanding of controls on the present-day seasonality, it is difficult to analyse whether model projections of shifts in the seasonality of Congo Basin evaporation are trustworthy (Berg and Sheffield 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The citizen science study presented here provides information on four widespread, common tropical species, which can potentially serve as references for future changes in phenology. leaf-out may be triggered, instead, by photoperiod or preceding the onset of monsoons across different latitudes (Adole et al, 2019;Elliott et al, 2006;Ryan et al, 2017). In SeasonWatch, however, we were…”
Section: Discussionmentioning
confidence: 72%